The effect of industrial work practice, guidance intensity of industrial side, and vocational competence on working readiness of grade XII students of banking program, Vocational High School Perbankan, Pekanbaru - Dwi Yana Putri; Sutarto Sutarto (Jurnal Pendidikan Vokasi, 2018)
This study aimed to find out the effect of: (1) industrial work practice, (2)guidance intensity of industrial side, (3)vocational competence, and (4) industrial work practice,guidance intensity of industrial side, and vocational competence on the working readiness of students of Vocational High School (VHS) PerBankan Pekanbaru. This research was ex-post facto research. The population was all students of class XII Program of Banking in the academic year of 2017/2018 which comprised 106 students who followed industrial work practice. A sample of 83 students was processed using the Proportional Random sampling technique. Prior to doing research, the instrument first validated the expert. After validated experts tested the validity and reliability to determine the valid and reliable instrument items. Data analyst technique used is descriptive research method, prerequisite test, and regression analysis. The results showed that: (1) industrial work practice (x1) has a positive and significant effect on students'working experience (y) evidenced by thitung ≥ ttabel (2,414 > 1,98) contribution of 27,63%; (2) the guidance intensity of industrial side (x2) had a positive and significant effect on students'working readiness (y) evidenced by thitung ≥ ttabel (2,822 > 1,98) contribution of 21,03%; (3) vocational competence (x3) had a positive and significant effect on students'working readiness (y) evidenced by thitung ≥ ttabel (2,348 > 1,98) contribution of 2,46%; (4) industrial work practice, guidance intensity of industrial side, and vocational competence simultaneously had a positive effect on students'working readiness (y) evidenced by Fhitung ≥ Ftabel(16,235 > 3,11) with contribution of 51,12%. The rest 48,88% was determined by other factors.